Antifungal Activity of Maytenin and Pristimerin - Gullo, Fernanda P. [UNESP]; Sardi, Janaina C. O. [UNESP]; Santos, Vania A. F. F. M. [UNESP]; Sangalli-Leite, Fernanda [UNESP]; Pitangui, Nayla S. [UNESP]; Rossi, Suelen A. [UNESP]; de Paula e Silva, Ana C. A. [UNESP]; Soares, Luciana A. [UNESP]; Silva, Julhiany F. [UNESP]; Oliveira, Haroldo C. [UNESP]; Furlan, Maysa [UNESP]; Silva, Dulce H. S. [UNESP]; et al. (Hindawi Publishing Corporation, 2012)
Fungal infections in humans have increased alarmingly in recent years, particularly in immunocompromised individuals. Among the infections systemic candidiasis, aspergillosis, cryptococcosis, paracoccidioidomycosis, and histoplasmosis mortality are more prevalent and more severe in humans. The current high incidence of dermatophytosis is in humans, especially as the main etiologic agents Trichophyton rubrum and Trichophyton mentagrophytes. Molecules pristimerin and maytenin obtained from the plant Maytenus ilicifolia (Celastraceae) are known to show various pharmacological activities. This study aimed to evaluate the spectrum of antifungal activity of maytenin and pristimerin and their cytotoxicity in human keratinocytes (NOK cells of the oral mucosa). It was concluded that the best spectrum of antifungal activity has been shown to maytenin with MIC varying from 0.12 to 125 mg/L, although it is also active with pristimerin MIC ranging between 0.12 and 250 mg/L. Regarding the toxicity, both showed to have high IC50. The SI showed high pristimerin against some species of fungi, but SI maytenin was above 1.0 for all fungi tested, showing a selective action of fungi. However, when comparing the two substances, maytenin also showed better results. The two molecules can be a possible prototype with a broad spectrum of action for the development of new antifungal agents.